Unloaded shape identification of human cornea by variational shape optimization. Issue 15 (18th November 2018) - Otani, Tomohiro; Tanaka, Masao
Abstract: The present study proposes a computational method to identify the unloaded corneal shape based on the prescribed surface profile of the cornea acquired from in vivo measurements. Variational shape optimization of the unloaded corneal shape was formulated to satisfy that the corneal shape at the mechanical equilibrium state in the physiological situation corresponded to the prescribed surface profile. The shape variation was calculated using the Lagrange multiplier method with a finite element solution. Numerical solution showed that the optimized corneal shape was in excellent agreement with the prescribed surface profile of the cornea without μm-scale surface irregularities.